Antibody-dependent enhancement of Coronavirus (2020)
Antibody-dependent enhancement (ADE) exists in several kinds of virus. It has a negative influence on antibody therapy for viral infection. This effect was first identified in dengue virus and then was also described for coronavirus. The rapid spread of the newly emerged 2019 novel coronavirus (COVID-19) has sickened over 3.8 million people across the globe up to now. The novel coronavirus causes great challenge and arouses a wave of panic. In this review, antibody-dependent enhancements in dengue virus and two kinds of coronavirus are summarized. Solutions for the effects are mentioned, too. We also speculate that antibody-dependent enhancement may exist in COVID-19.